2023
DOI: 10.1093/sleep/zsad099
|View full text |Cite
|
Sign up to set email alerts
|

Is it wiser to train in the afternoon or the early evening to sleep better? The role of chronotype in young adolescent athletes

Abstract: Study objectives To examine the effect of the timing of high-intensity exercise (afternoon vs. evening) on adolescent athletes’ bedtime psychological state, sleep quality, sleep staging, and next-day wellness/sleepiness according to chronotype. Methods Forty-two young athletes (morning type: n =12, intermediate type: n =14; evening type: n=16) completed a randomized crossover study under free-living conditions. The counterbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…TST also tended to be lower following endurance exercise. Our results align with recent findings from Saidi and others ( Saidi et al, 2023 ) showing lower sleep efficiency (−1.50%) following high intensity evening exercise, although the intensity was moderate in the current study. Both endurance and resistance exercise conditions also led to greater theta power compared to the control condition during N2 sleep stage.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…TST also tended to be lower following endurance exercise. Our results align with recent findings from Saidi and others ( Saidi et al, 2023 ) showing lower sleep efficiency (−1.50%) following high intensity evening exercise, although the intensity was moderate in the current study. Both endurance and resistance exercise conditions also led to greater theta power compared to the control condition during N2 sleep stage.…”
Section: Discussionsupporting
confidence: 93%
“…Seemly, Saidi and others investigated the effects of afternoon compare to evening exercise in young adolescent athletes and has shown that evening exercise led to lower sleep efficiency and longer sleep onset latency. Such effects were also moderated by chronotype (Saidi et al, 2023). Therefore, the effects of acute exercise performed in the evening is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate choice of when to exercise under sleep‐restricted conditions is another important consideration, given the potential time‐of‐day specific effects of exercise (Grgic et al, 2019; Saner & Lee, 2020) and considering that the influence of sleep restriction on mood and alertness, likely increases throughout the day. In this regard, a recent study demonstrated that individual chronotype was an important consideration for interpreting the effect of exercise timing on psychological state and sleep quality (Saidi et al, 2023). Although participants in the current study were classified as either moderate or intermediate chronotypes, this should be another consideration in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this may result in athletes shortchanging sleep due to early AM or late PM training sessions. Furthermore, late PM training may lead to heightened pre-sleep arousal [ 6 , 22 ], which can translate into difficulties with sleep initiation. These factors highlight the augmented risk that marathoners are likely to face for poor sleep health.…”
Section: Discussionmentioning
confidence: 99%